2014
DOI: 10.1002/iroh.201301728
|View full text |Cite
|
Sign up to set email alerts
|

Ostracod communities associated to aquatic macrophytes in an urban park in Rome, Italy

Abstract: The relationship between ostracod and macrophyte communities has been seldom studied, especially in urban parks. The main purpose of this research is to explore such a relationship in the area of Rome (Italy), and in particular in the Appia Antica Regional Park, to provide information about the environmental characteristics influencing both the assemblages and to document for the first time the distribution of freshwater ostracods in an area inside the city of Rome. The survey has considered different water bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…This suggests that ostracod species do not always have a preference for complexity and/or plant species. Association among macrophytes and ostracod communities also was evidenced by previous papers Mazzini et al 2014), which showed that some ostracods have preferences for certain plant species, while others were found in a wide range of habitats.…”
Section: Discussionsupporting
confidence: 70%
“…This suggests that ostracod species do not always have a preference for complexity and/or plant species. Association among macrophytes and ostracod communities also was evidenced by previous papers Mazzini et al 2014), which showed that some ostracods have preferences for certain plant species, while others were found in a wide range of habitats.…”
Section: Discussionsupporting
confidence: 70%
“…Thus, in this study, we evaluate the current status of the spreading and invasiveness of L. minuta outside its original range, considering in particular: (i) the speed with which the species has spread throughout Europe and thus its ability to colonize and spread into new areas; (ii) the capability of L. minuta to compete with its congeneric native species L. minor in sites in Central Italy. The choice of analysing the interaction of L. minuta with L. minor is related to the fact that L. minor is the most common native duckweed in Europe (Landolt ), morphologically very similar to L. minuta (Ceschin et al, ), and often found in association with it, sharing the same environment typology for analogous ecological requirements (Landolt ; Sburlino et al, ; Iamonico et al, ; Mazzini et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The same has been recognized by Kiss (2007) at Lake Fehér (Hungary). It is particularly interesting to confirm the strict relation between some species and free-floating macrophytes, already recognized by Kiss (2007) and Mazzini et al (2014a). L. inopinata dominates areas with low presence of C. torosa and C. (N.) angulata, slightly deeper (around 150-210 cm) (samples in the low right quarter of the NMDS plot, Fig.…”
Section: Discussionmentioning
confidence: 59%